2007
DOI: 10.1109/tnano.2007.908491
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Mechanical and 3-D Monte Carlo Simulation of Silicon Nanowire MOSFETs

Abstract: In this paper we report on a general methodology to investigate nanowire MOSFETs based on the coupling of mechanical simulation with 3-D real-space Monte Carlo simulation. The Monte Carlo transport model accounts for both strain silicon and quantum mechanical effects. Mechanical strain effects are accounted for through an appropriate change of the anisotropic band structure computed with the empirical pseudopotential method. Quantum effects are instead included by means of a quantum mechanical correction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Several works on silicon nanowires have shown that these effects may influence substantially their electrical and mechanical properties. In particular, for diameter smaller than 20 nm, many physical quantities such as the Young's modulus, the Poisson ratio, the electron and hole effective mass, the band gap and the mobility are strongly affected with respect to bulk data (Leu et al, 2006;Leu et al, 2008;Ghetti et al, 2007). However, in this study, to compare with available experimental data, we simulated structures with minimum thicknesses of 80 nm which is much larger than the critical size mentioned above.…”
Section: Giant Piezoresistance Effect In P-si Nanowiresmentioning
confidence: 97%
“…Several works on silicon nanowires have shown that these effects may influence substantially their electrical and mechanical properties. In particular, for diameter smaller than 20 nm, many physical quantities such as the Young's modulus, the Poisson ratio, the electron and hole effective mass, the band gap and the mobility are strongly affected with respect to bulk data (Leu et al, 2006;Leu et al, 2008;Ghetti et al, 2007). However, in this study, to compare with available experimental data, we simulated structures with minimum thicknesses of 80 nm which is much larger than the critical size mentioned above.…”
Section: Giant Piezoresistance Effect In P-si Nanowiresmentioning
confidence: 97%
“…Number of attempts have been accomplished for modeling and simulation of SNWTs with numerical methods that are based on different models like selfconsistent numerical model, Monte Carlo transport model, non equilibrium Green function (NEGF) approach and etc [6][7][8][9][10]. These methods are complicated and take a lot of simulation times.…”
Section: Introductionmentioning
confidence: 99%
“…However, the solution time and memory requirements can be significantly reduced using an optimised device mesh. Second, some of the novel thin-body transistor architectures, which are expected to replace the conventional bulk transistors during the process of scaling into nanometre dimensions, do not have planar geometry [6]. For example, the TriGate FinFET architecture, shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…MC device simulators built using tetrahedral elements have been presented in the past [6,10] but, to our best knowledge, the problem of the self-forces has not been treated. This is an effect which appears in self-consistent simulations and leads to artificial forces and will be discussed in Section 3.…”
Section: Introductionmentioning
confidence: 99%